Acoustic-Phonetic Mismatches Impair Serial Recall of Degraded Words. Issue 1 (2nd April 2020) - Bosen, Adam K.; Monzingo, Elizabeth; AuBuchon, Angela M.
ABSTRACT: Sequences of phonologically similar words are more difficult to remember than phonologically distinct sequences. This study investigated whether this difficulty arises in the acoustic similarity of auditory stimuli or in the corresponding phonological labels in memory. Participants reconstructed sequences of words which were degraded with a vocoder. We manipulated the phonological similarity of response options across two groups. One group was trained to map stimulus words onto phonologically similar response labels which matched the recorded word; the other group was trained to map words onto a set of plausible responses which were mismatched from the original recordings but were selected to have less phonological overlap. Participants trained on the matched responses were able to learn responses with less training and recall sequences more accurately than participants trained on the mismatched responses, even though the mismatched responses were more phonologically distinct from one another and participants were unaware of the mismatch. The relative difficulty of recalling items in the correct position was the same across both sets of response labels. Mismatched responses impaired recall accuracy across all positions except the final item in each list. These results are consistent with the idea that increased difficulty of mapping acoustic stimuli onto phonological forms impairs serial recall. Increased mapping difficulty could impair retention of memoranda and impede consolidation into phonological forms, which would impair recall in adverse listening conditions.